Spolia in fortifications and the common builder in late antiquity - Frey, Jon M. (Mnemosyne, Supplements, 2015)
Through intensive surveys of three fortifications in late Roman Greece, Frey reveals the untapped potential of spolia in demonstrating the critical role played by non-elites in bringing about the architectural and social changes that mark the end of classical antiquity. As his analysis demonstrates, when studied less as displaced objects to be classified by type and more as evidence for the construction process itself, spolia offer a unique opportunity to examine the ways in which common builders met the challenge of using pre-existing building materials to meet their contemporary architectural needs. This "bottom-up" approach offers an alternative to the traditional view that attributes change and innovation only to the genius of prominent individuals known to us in historical sources.